A Late Miocene potential neobalaenine mandible from Argentina sheds light on the origins of the living pygmy right whale - Buono, Mónica Romina (2014)
The origins and evolutionary relationships of the pygmy right whale (Caperea marginata),the only living member of the Neobalaeninae, have been the subject of a long-standing debate. This phylogenetic uncertainty is compounded by a limited neobalaenine fossil record. Here, we report a Late Miocene mysticete mandible from Patagonia, Argentina and provisionally refer it to Neobalaeninae, gen. et sp. indet. The new material represents only the third report of a fossil neobalaenine, and the first fossil occurrence of this lineage in the southwestern Atlantic. It is also the oldest specimen so far reported, thus corroborating the idea of an early divergence time for neobalaenines.